Restorative reconstruction after total mesorectal excision for rectal cancer is associated with significant bowel dysfunction from initial presentation() - Ivatury, Srinivas J. (Surg Open Sci, 2020)
BACKGROUND: Patients often desire restorative reconstruction following total mesorectal excision. Reconstruction has become synonymous with providing high-quality rectal cancer care. However, the bowel functional outcomes of restoration from presentation are unknown. We aimed to evaluate the bowel functional effects of rectal cancer treatment from presentation through surveillance. METHODS: This was a retrospective cohort study from 2014 to 2019 using prospectively collected data. Patients underwent treatment for rectal adenocarcinoma including restorative reconstruction. Patients completed the validated Colorectal Functional Outcome questionnaire during clinic visits (1) at presentation, (2) after neoadjuvant therapy, (3) after restoration of continuity, and (4) at surveillance. Scores range from 0 to 100 with a higher score indicating worse bowel function. RESULTS: Sixty-eight patients (age: 62 ± 12 years, 40% female) were included. The mean tumor height was 7 ± 4 cm with 85% symptomatic. Bowel function did not worsen from presentation to after neoadjuvant therapy in Total Colorectal Functional Outcome and most domain scores; there was improvement in frequency and stool-related aspects. Bowel function worsened in all scores from after neoadjuvant to restoration of continuity (mean anastomotic height: 5 ± 2 cm); there were similar findings between presentation and restoration of continuity. At surveillance, there was improvement in most domains compared with restoration of continuity. There remained significant worsening of incontinence, social impact, and need for medication scores at surveillance compared with presentation. CONCLUSION: Restorative reconstruction after total mesorectal excision is associated with significant bowel dysfunction. For some patients, restorative reconstruction may not be high-quality rectal cancer care.